Pemanfaatan Mangrove sebagai Kegiatan Pengelolaan Limbah Berbasis Masyarakat dan Pemanfaatan Hasil Tambak di Desa Tambakbulusan Kabupaten Demak - Sari Listyorini; Dinalestari Purbawati; Ilham Ainuddin (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Mangrove is a type of plant that has a fairly strong root structure and can absorb storm waves and tsunamis. Mangroves function as abrasion protectors. It turns out that they have many benefits, one of which is processed into healthy food. Mangrove is one of the plants that thrives around Glagah Wang Beach, Tambakbulusan Village, where it can be used as a basic ingredient for processed food or healthy snacks. Another potential that is owned is the existence of fish ponds that are capable of producing one of which is milkfish. Milkfish can be used with various processed foods, one of which is dimsum. This Community Service aims to increase the potential of the local village to increase the attractiveness of culinary tourism around Glagah Wangi beach by facilitating training on mangrove waste management and pond products in the form of processed food with added value. The target of this community service is aimed at PKK mothers in Tambakbulusan Village with the hope of increasing knowledge and skills in processing mangrove and fish ingredients into healthy and economically valuable snacks